2014
DOI: 10.1007/s00181-014-0801-2
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of economic convergence in the European Union

Abstract: Reproduction permitted only if source is stated.ISBN 978-3-86558-941-5 (Printversion) Non-technical summary Western European countries took major steps toward economic integration in recent decades, including the liberalization of capital and labor markets and the foundation of the European Economic and Monetary Union (EMU). The 1992 Maastricht Treaty set an agenda for macroeconomic convergence prior to entering the monetary union, and the European Commission has put forward numerous policy initiatives aimed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
94
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(108 citation statements)
references
References 61 publications
9
94
0
5
Order By: Relevance
“…Since panel data techniques are commonly used in estimation, researchers often decide to divide panels into more homogenous a priori subgroups, like EU15, EMU, CEE, SEE, CIS, the Visegrad group, Baltic States and others. Borsi and Metiu (2015) investigate economic convergence in real income per capita between 27 EU countries in 1970-2010 using a non-linear latent factor framework. Their results suggest no overall real income per capita convergence in the EU, but subgroups that converge to different steady states are identified using an iterative testing procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Since panel data techniques are commonly used in estimation, researchers often decide to divide panels into more homogenous a priori subgroups, like EU15, EMU, CEE, SEE, CIS, the Visegrad group, Baltic States and others. Borsi and Metiu (2015) investigate economic convergence in real income per capita between 27 EU countries in 1970-2010 using a non-linear latent factor framework. Their results suggest no overall real income per capita convergence in the EU, but subgroups that converge to different steady states are identified using an iterative testing procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Main Lithuanian fruits and berries import partners after accessing EU became Spain and Italy. It corresponds to some alternative economic ideas [56] that newly accepted EU members become an open market for products from older member states.…”
Section: Changes In Growing Of Health-friendly Food Crops and Productmentioning
confidence: 99%
“…Particularly, the "success story" could be heard in the context of Eastern-European regions catching up with the advantageous regions of the older EU states (Bosker, 2009). Multiple studies have found evidence of decreasing income disparities over time in Europe, both before and after the EU enlargement (Borsi and Metiu, 2015;Ezcurra et al, 2005;Ezcurra and Rapún, 2007;Fingleton, 1999;Maza et al, 2012;Monfort, 2008;Neven and Gouymte, 1995). However, a notable part of the reduction in regional disparities that is attributed to the Cohesion Policy, may have been explained by different dynamics in regional population structures that most studies on economic cohesion tend to overlook (Crespo Cuaresma et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%